Ministry of Finance Decree No 778 Of The Year 2010 Amending Certain Provisions Of The Executive Regulations Of The Income Tax Law Promulgated By The Minister Of Finance Decree No. 991 Of The Year 2005 = وزارة المالية قرار رقم 778 لسنة 2010 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على الدخل الصادرة بقرار وزير المالية رقم 991 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.